WOMEN, MATERNITY AND MENTAL HEALTH - Teixeira Ramos Tavares, Fabiana (LINKSCIENCEPLACE, 2026)
This study aims to deepen the understanding of the reality of women in Brazil, highlighting the factors associated with their mental health. While mental health is a challenge for most mothers, single mothers face additional obstacles. IBGE data indicate that in Brazil more than 11 million women are solo mothers, with more than 1/3 of families headed by women, with 63% of them living below the poverty line (Caldas, 2021). Delboni (2021) points out that domestic, psychological and obstetric violence, in addition to moral harassment, increase the risk to pregnant women’s health. Guimaraes et al. (2019) indicate that the incidence of mental health problems among pregnant women in Brazil varies from 31% to 41%, being higher in the central region of the country. Guerra et al. (2014) discuss the physical and psychological implications of pregnancy, which, without adequate monitoring, can pose risks to the health of the mother and child. This study adopts a deductive and qualitative approach to analyze the impact of gender inequality on female mental health. Based on a bibliographical review, the research examines scientific articles, dissertations and theses to explore the complex relationship between gender inequality, the pandemic and the mental problems faced by women. The urgency to achieve gender equality and an equitable distribution of domestic responsibilities is justified as an imperative of social justice and a commitment to Human Rights. The study highlights the need to invest in public health and school infrastructure, promote the equal participation of women in the labor market, implement humanized care policies during pregnancy, childbirth and postpartum, and create family support structures. These measures can help ensure that maternal mental health ceases to be a public health problem, ensuring a more favorable environment for the well-being of mothers, especially those who face additional challenges as solo mothers.